Analysis of the dominant mutation N188T of human connexin46 (hCx46) using concatenation and molecular dynamics simulation. Issue 5 (23rd March 2019) - Schadzek, Patrik; Stahl, Yannick; Preller, Matthias; Ngezahayo, Anaclet
Abstract : Connexins (Cx) are proteins that form cell‐to‐cell gap junction channels. A mutation at position 188 in the second extracellular loop (E2) domain of hCx46 has been linked to an autosomal dominant zonular pulverulent cataract. As it is dominantly inherited, it is possible that the mutant variant affects the co‐expressed wild‐type Cx and/or its interaction with other cellular components. Here, we proposed to use concatenated hCx46wt‐hCx46N188T and hCx46N188T‐hCx46wt to analyze how hCx46N188T affected co‐expressed hCx46wt to achieve a dominant inheritance. Heterodimer hCx46wt‐hCx46N188T formed fewer gap junction plaques compared to homodimer hCx46wt‐hCx46wt, while the hCx46N188T‐hCx46N188T homodimer formed almost no gap junction plaques. Dye uptake experiments showed that hemichannels of concatenated variants were similar to hemichannels of monomers. Molecular dynamics simulations revealed that for docking, the N188 of a protomer was engaged in hydrogen bonds (HBs) with R180, N189, and D191 of the counterpart protomer of the adjacent hemichannel. T188 suppressed the formation of HBs between protomers. Molecular dynamics simulations of an equimolar hCx46wt/hCx46N188T gap junction channel revealed a reduced number of HBs between protomers, suggesting reduction of gap junction channels between lens fibers co‐expressing the variants. Abstract : Concatenated hCx46wt‐hCx46N188T formed fewer gap junction plaques as compared to concatenated hCx46wt‐hCx46wt. Molecular dynamics predicted that the presence of hCx46N188T reduced the sum of hydrogen bridges between protomers in connexons of adjacent cells. Reduction of the hydrogen bonds impairs connexon docking between cells expressing both isoforms. The data are compatible with the dominant inheritance of the hCx46N188T mutation.